Research on the construction method of quasi-complementary sequence sets for peak-to-average power ratio reduction of multicarrier signal - Yubo LI; Meiyue WANG; Tao LIU; Xiaoyu CHEN (Tongxin xuebao)
To solve the problem of limited number of sequences in the mutually orthogonal complementary code set and high peak-to-average power ratio (PAPR) in MC-CDMA system, a construction of asymptotically optimal a periodic binary QCSS with low column vector PAPR was proposed.The obtained QCSS with asymptotically optimal parameters had more sequences than the existing QCSS due to the designed mapping set.The QCSS based on the orthogonal Golay sequence set had column vector PAPR of at most 2.Experimental simulation results show that the constructed sequence sets can effectively reduce the time-domain MC-CDMA signal PAPR to 3 dB and have good bit error rate performance.